TINJAUAN PROMOSI OBJEK WISATA PANTAI USAMAR LILIBOOI - Angel Sohilait; Imelda Talahatu (Jurnal Administrasi Terapan, 2023)
Proper tourism promotion can increase the number of visits and will have an impact on regional development of the tourist attraction itself. Due to the lack of updates regarding tourist information in this area, a good promotional strategy is needed so that the vision and mission of regional tourism can be realized. The purpose of this writing is to provide an overview of the promotions carried out to increase tourist interest in Usama beach. The method of data obtained is that the author uses a qualitative data analysis method using data in the form of information from the research location and using a theoretical promotion mix approach according to experts. The conclusion of this research is that in introducing Usama Beach as a tourist attraction, it is necessary to carry out appropriate promotions by implementing a promotional mix consisting of: advertising, personal selling, publicity and public relations.Keywords : Promotion of Tourist Attractions